Thermo-Oxidative Stability Evaluation of Bullfrog (Rana catesbeiana Shaw) Oil - Renata Rutckeviski; Francisco H. Xavier-Júnior; Andreza R.V. Morais; Éverton N. Alencar; Lucas Amaral-Machado; Julieta Genre; Amanda D. Gondim; Eryvaldo S.T. Egito (Molecules, 2017)
Bullfrog oil (BO), a natural product obtained from recycling of adipose tissue from the amphibian Rana catesbeiana Shaw, has been recently evaluated as a therapeutic activity ingredient. This work aimed to evaluate the long-term and accelerated thermal oxidative stabilities of this product, which is a promising raw material for emulsion technology development. BO was extracted from amphibian adipose tissue at 70 °C with a yield of 60% ± 0.9%. Its main fatty acid compounds were oleic (30.0%) and eicosapentaenoic (17.6%) acids. Using titration techniques, BO showed peroxide, acid, iodine and saponification indices of 1.92 mEq·O2/kg, 2.95 mg·KOH/g oil, 104.2 g I2/100 g oil and 171.2 mg·KOH/g oil, respectively. In order to improve the accelerated oxidative stability of BO, synthetic antioxidants butylhydroxytoluene (BHT) and buthylhydroxyanisole (BHA) were used. The addition of BHT increased the oxidation induction time compared to the pure oil, or the oil containing BHA. From the results, the best oil-antioxidant mixture and concentration to increase the oxidative stability and allow the oil to be a stable raw material for formulation purposes was derived.